Chapter EAEA Younger Staff Training as a Learning Journey - Tursi, Silvia (Studies on Adult Learning and Education, 2020)
The EAEA Younger Staff Training is a good example of a successful initiative that encour-ages the professional development of adult education staff, builds new collaborations, and explores the diversity of policy and practice in adult learning in Europe. Organized annually since 2011, the training programme has undergone several modifications over the years to adapt to the changing needs of adult education professionals. The paper looks at the content and structure of the programme, with specific attention to how these have evolved and the rationale behind the changes. It also briefly describes why the training programme continues to be successful and its benefits for both the participants and the organizers.